Using Student Test Scores to Award Merit Pay: A Look at the 2012 Pay-for-Performance Program for Idaho Schools - Gary Lee Storie; Peter R. Denner (Arizona State University, 2015)
In the fall of 2012, Idaho implemented a plan to award bonus pay to schools whose students demonstrated academic growth based on the Betebenner (2008) method.  This study examined the relationship of the amount of bonus paid to a school, the percentage of students from low income families associated with a school, and the location of the school (urban, suburban, town, or rural).  Using hierarchical set regression, a statistically significant negative relationship was found between the percentage of students eligible for subsidized meals and per pupil school bonus pay.  When school location was added as a predictor, rural school location emerged as a positive predictor of the amount of per pupil bonus money received by a school.  The percentage of students eligible for subsidized meals also predicted whether a school received any bonus money.